Investigating the Moderating Effects of Gender and Generation on the Link of Quality Products Perception and Online Shopping Motivation - Rahardja, Conny Tjandra; Rohman, Isnanda Zainur; Puspa, Jofi (International Journal of Psychosocial Rehabilitation, 2020)
This study describes some findings concerning the influence of consumers’ perception for quality products on the motivation of online shopping with gender and generation as moderators. This study involved a total of 521 respondents spread out over some regions of Indonesia. Collected data were processed by using the regression analysis. This study found that in the absence of moderation variables the consumers` perception of quality products (KP) had a positive and significant effect on the motivation to shop online (OS), because every consumer prefers a quality product. The subsequent analysis focusing on the effect of KP on OS adjusted for gender and generation revealed that: (1) in men group, the consumer’s perception of quality products (KP) influences the motivation to shop online (OS) slightly stronger than in women; (2) in the B-Boomers’ generation there was no effect of KP on the OS; (3) in the generation X, Y, Z there was a strong effect of KP on the OS. Finally, this effect was more pronounced in generation X as compared to Z and that this effect in Z was still stronger than in generation Y.